Validity and reliability test of the knowledge level questionnaire of cancer patients undergoing radiotherapy - Hanum, Fathiya Juwita; Machmud, Rizanda; Gondhowiardjo, Soehartati; Khambri, Daan; Harahap, Wirsma Arif; Elliyanti, Aisyah; Firdawati, Firdawati; Semiarty, Rima (Poltekkes Kemenkes Bandung, 2026)
Background: Radiotherapy is one of the main modalities in cancer treatment. The success of this therapy is strongly influenced by the knowledge of patients about the disease and radiotherapy. The researcher developed a questionnaire to measure the level of knowledge among cancer patients undergoing radiotherapy. Objective: This study aimed to assess the validity and reliability of a knowledge-level questionnaire for cancer patients receiving radiotherapy at Dr. M. Djamil General Hospital, Padang. Methods: This research employed a quantitative approach with a cross-sectional design. A total of 30 cancer patients undergoing radiotherapy were included as respondents using a consecutive sampling technique. The questionnaire instrument was developed by the researcher and consisted of 25 items covering five domains of knowledge: cancer, radiotherapy, side effects, self-care, and nutrition. Results: Validity testing was conducted using Pearson’s correlation analysis, while reliability was assessed using Cronbach’s Alpha. Out of the 25 items, 19 were statistically valid (p<0.05), with correlation coefficients (r) ranging from moderate to strong (0.470–0.745). The Cronbach’s Alpha value for the valid items was 0.904, indicating excellent reliability. Conclusion: The developed questionnaire was proven to be both valid and reliable for measuring the knowledge level of cancer patients undergoing radiotherapy. This instrument has the potential to be used in clinical practice and research to support more targeted educational interventions.